Telaah Dampak Boikot Produk Amerika terhadap Perekonomian Nasional - Heri Sudarsono (Universitas Islam Indonesia, 2008)
A boycott plan of American products should consider national economy. The Americanproducts have contributed to the increase of national economic growth, because humanand natural resource managements of Indonesia have depended on the American products.The boycott action would decrease economic growth, because it would decreasedemands and increase unemployment. Besides, the action, on one side, would not beeffective since economic relation between Indonesia and United States has been legitimizedby both regional and international trade organization. On the other side, the dependencyof Indonesia on American products have been relatively high, as seen from thevolume of non oil and gas export-import between the two countries. Government economicpolicy is affected by cooperation with other countries, and therefore, the boycott actionwould not affect the decrease of consumption of American products.Keywords: boycott, economy, legitimacy, trade.